Memory complaints are frequent but qualitatively different in young and elderly healthy people - Ginó, Sandra (2010)
Background: Subjective memory complaints are frequently reported by the elderly. There is less information about the characterization of subjective memory complaints in young people. Objective: To determine different memory complaints between young and elderly people with the use of the Subjective Memory Complaints (SMC) scale. Methods: Participants were volunteers attending a health itinerant unit, a blood donor centre, a leisure centre for retired people, a senior citizens college or university. All participants were questioned about their own memory abilities using the SMC scale and assessed for the presence of depressive symptoms. Results: Nine-hundred and forty-six subjects aged 18–92 years were included in the study. The mean total score on the SMC scale was 4.89 +- 3.03, and 75.9% of the participants had at least minor complaints about their memory. Older people had more general memory complaints and reported they were more likely to become transiently confused, whereas younger people reported they were more frequently told by others that they were forgetful and would more often take notes. Conclusions: Memory complaints were frequent both in young and elderly subjects, but the detailed assessment revealed age-related differences in the type of complaints.